2022
DOI: 10.1155/2022/8130373
|View full text |Cite
|
Sign up to set email alerts
|

Extensive HPV Genotyping Reveals High Association between Multiple Infections and Cervical Lesions in Chinese Women

Abstract: Objective. The relationship between human papillomavirus (HPV) and cervical lesions has been extensively elucidated, but infection with multiple genotypes is less investigated due to methodology limitations. In the current study, with a method of genotyping 21 HPVs in a routine cervical screening population, we aimed to investigate the prevalence and diversity of HPV infections in Chinese women and further evaluate the impact of multiple infections of HPV on cervical lesion progression. Methods. Totally, 73,59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…In total, 33.2% of HR-HPV-positive patients were infected with multiple HR-HPVs in our study, which is within the range of 26.3% and 43.2% that has been previously reported [ 32 , 33 ]. We found that a higher incidence of HSIL+ in patients with single infections than those with multiple infections.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In total, 33.2% of HR-HPV-positive patients were infected with multiple HR-HPVs in our study, which is within the range of 26.3% and 43.2% that has been previously reported [ 32 , 33 ]. We found that a higher incidence of HSIL+ in patients with single infections than those with multiple infections.…”
Section: Discussionsupporting
confidence: 82%
“…Other data highlight the importance of the type of HPV infection. For example, a single infection with HPV 16 is more virulent than a multiple-infection pattern, while for HPVs 52, 53, 56, 51, 39, 66, 59, 68, and 35, a multiple-infection pattern is more likely to develop into HSIL+ than a single infection [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…HPV18 and HPV31 were categorized under the 5 most common HPV genotypes that affect women worldwide (Pimple and Mishra, 2022). Moreover, HPV18 and HPV16 are the most potent strains that are responsible for over 70% of the cases of cervical and head, and neck cancers worldwide (Yu et al, 2022). The most potent oncogenes associated with HPV 18 are E6/E7 (Tian et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Persistent infection with HR-HPV genotypes represents the major concern about cervical cancer burden in these regions. HR-HPV subtypes 16, 18, 31, 58, and HR-HPV subtypes include 16,18,31,33,45,35,52,56,39,51,68,and 59. Moreover,HPV 53,66,26,73, and 82 are regarded as potential HR-HPV subtypes (Zhong, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation